Application Of The "Rule of Halves" For Hypertension as An Assessment Tool in An Urban Slum at Davangere - Varadaraja Rao BA; Arun Daniel J (Medsci Publications, 2014)
Background: The 'rule of halves' for hypertension states that: 'half the people with high blood pressure are not known ("rule 1"), half of those known are not treated ("rule 2") and half of those treated are not controlled ("rule 3")' Aim: To evaluate the applicability of 'rule of halves' as an assessment tool for detecting the status of awareness, management and control measures for hypertension in the community. Methodology: A community-based cross-sectional study was conducted among adults aged 30 years and above residing in urban field practice areas of S.S Institute of Medical Sciences, Davangere. A sample of 1000 individuals who were aged 30 years and above was selected by systematic random sampling. Using a structured questionnaire, the basic information and history regarding diagnosis and treatment of hypertension was collected. Blood pressure,height and weight were recorded. Result: The overall prevalence of hypertension in this population was 36.7% (367/1000). Of these 367 individuals with hypertension, only 127 (34.6%) were known hypertensives. Of the 127 known hypertensives, 87 subjects (68.5%) were under any kind of antihypertensive therapy. Of these 87 individuals, only 21 (24.1%) had blood pressure under control. Conclusion: The 'rule of halves' when taken as a standard of measurement showed that the studied population hadpoor awareness, comparatively better treatment and inadequate control of Hypertension.